STRATEGY ENGLISH PHONOLOGY: TEACHING TO BEGGINNER'S GUIDE - Marpaung, Rismayani; Amru, Aisyah; Geovani, Celli; Lubis, Yani (PT Rahis Cendekia Indonesia, 2025)
Phonology is an important aspect of learning English as a foreign language, especially for beginners. Understanding the English sound system not only helps improve pronunciation, but also strengthens listening and speaking skills. However, many students experience difficulties due to the phonological differences between their native language and English. This article aims to present effective strategies in teaching phonology based on recent findings. The method used is a literature study by analyzing various relevant literature sources. The results show that strategic approaches such as the use of AI-based technology, minimal pair practice, articulation visualization, as well as providing continuous feedback can significantly improve students' phonological awareness. Other strategies such as reading rhyming poems, singing rhyming songs, and sound manipulation exercises also play an important role in helping students recognize and produce sounds better. With targeted and needs-based phonology teaching, communication skills in English can be effectively improved.